PENGARUH PENGGUNAAN LSHX TERHADAP PERFORMA MESIN PENDINGIN DENGAN LAJU ALIRAN MASSA YANG SAMA PADA KONDISI TRANSIENT - Redaksi Tim Jurnal (JURNAL POWERPLANT, 2017)
There are three things that affect the development of of vapor compression refrigeration system : energy saving, non-ODP and non-GWP refrigerant charges. Keep in mind that the effect on GWP refrigerant and ODP substances occurs only when the substance is released into the atmosphere due to leakage in the refrigeration machine or replacement and recycling of refrigerant. Vapor compression refrigeration system is still used, as well as the type of refrigerant used predominantly of HCFC R22 and HFC R404A environmentally damaging and is scheduled to be removed. So to find an alternative refrigerant that is environmentally friendly and has a good refrigeration capacity such as by adding LSHX technology (Liquid Suction Heat Exchanger). LSHX technology is the use of heat exchanger equipment between the liquid line out the condenser and compressor inlet suction line. The present experimental used three refrigerant different i.e HFC R404A, as a comparison used to replace HCFC R22 and for replacement synthetic refrigerant used hydrocarbon R290 in the vapor compression refrigeration system with LSHX In transient conditions until steady conditions. The refrigeration system was charged with 2 kg of mass, 27oC ambient temperature, and for the calculation using software REFPROP 6. This research conducted in Refrigeration Workshop (Bengkel Pendingin) STT-PLN Jakarta. The results obtained showed the effect LSHX with same mass flow rate, trend the steady state temperature of evaporation HCFC R22 decreased of -16,7oC be -18,2oC, HFC R404A of -19,9oC be -22,2oC and HC R290 of -24,2oC be -27,6oC. Increase the COP, for HCFC R22 from 3,29 to 3,39, HFC R404A from 2,76 to 2,85 and HC R290 from 3,43 to 3,50.